Epistemology Study: The Role of Christian Teachers Regarding Students Freedom in Learning: Kajian Epistemologi: Peran Guru Kristen terhadap Kebebasan Belajar Siswa - Neng Priyanti; Nabylla Sardy (Sekolah Tinggi Teologi Baptis Indonesia, 2021)
School epistemological belief is essential as it directly influences the goal and center of education. Following this logic, Christian education ideally aims to guide students to the knowledge of God as Christian epistemology believes that God is the source of knowledge. However, in teaching and learning practices, Christian teachers may be unaware of the world’s modern philosophy and thus unconsciously adopt the practices from the modern educational approach. As a result, the goal of Christian education can be shifted from God-centered to student-centered learning within progressive educational practice. Misleading knowledge and truth may bring schools away from the responsibility to fulfill God’s will in education. Thus, it is necessary for Christian teachers to guide students throughout the learning process to see God as the source of knowledge. This paper aims to critically discuss the Christian teachers’ role as a guide regarding students’ freedom in learning. To this end, this study employs a literature review method. The study concludes that Christian teachers can exercise the God-given authority to guide students in using their intellectual and free-will to serve God and others.